Melhoramento da produção de enzimas ligninocelulolíticas a partir de resíduos agrícolas da Amazônia - Silva, Sarah Raquel Silveira da (2015)
The rapid population growth and also of economic activities have generated a significant increase in waste, whether in solid, liquid and gaseous, with undesirable effects on the environment. Agricultural activities have intensified over the years and thus, organic waste are generated and accumulated in the environment causing the deterioration. Given this, have been sought sustainable alternatives using these residues to numerous economically viable purposes. The organic vegetable waste (bark, bran, seeds, bagasse) are made up of a lignocellulosic compound (cellulose, hemicellulose and lignin) and from the these, it is possible to produce various products with high added value such as amino acids, proteins, enzymes of interest for various industries, and they food industries (juices, cakes), textile industry, paper industry, etc. There are micro-organisms that produce lignocelulolítico an enzyme complex capable of degrading the components of the cell wall of the plant cell. These enzymes are of great interest for various industries, because through these, it is possible to optimize the production of products of interest. Therefore, 1% (1 g) of three Amazonian agricultural substrates (cupuaçu shells, passion fruit and cassava) underwent submerged cultivation in two salt solutions (Manachini and GLBN 40) in 125 ml Erlenmeyer flasks containing 20 ml of two different solutions minerals by the fungi Aspergillus niger, Penicillium sp. and in Basidiomycete 120h (5 days) and 240 hours (10 days). Enzymes were evaluated seven (CMCase, FPase, β-glucosidase, xylanase, lignin peroxidase, manganese peroxidase and laccase) where the A. niger was the best producer of CMCase, β-glucosidase and xylanase (7,295 IU/mL, 13,596 IU/mL and 33,653 IU/ml, respectively), Penicillium sp. was the best producer of FPase and Lignin peroxidase (0,126 IU/mL and 36.391 IU/L, restectivamente) and the Basidiomycete proved to be the best producer of manganese peroxidase and laccase (1.053 IU/L, 324,074 IU/L, respectively). Subsequently, A. niger which was the best producer of cellulases, was subjected to an experiment where the best substrates (passion fruit bark and cassava bark) were mixed and subjected to submerged culture with two salt solutions also merged in a matrix 9 proportions. The best ratio was R6: 4 S1:1. A new experiment was done with this ratio and the A. niger was subjected to a fungal consortium with basidiomycete checking for differences between two different methods of experiment. The final experiments showed improvement in the enzymatic production of manganese peroxidase and lignin peroxidase (1.570 IU/L and 11.610 IU/L ) compared to the values obtained by the two fungi in the initial experiment. KEY WORDS: Lignocellulolytic enzymes , Fungi amazonian, Enzymatic improvement